Language Policy In Algeria: An Outlook Into Reforms - Zakia Djebbari (Al-Lisaniyyat)
The query of language education policies in Algeria appears to be among the most crucial issues involved in current language research. It is believed that Algeria absorbed heavy colonial impact not only in its social life but also in its educational policy. The present paper attempts to deeply describe foreign language policy in Algerian education in general and at higher education in particular after the adaptation of the LMD system.